2011
DOI: 10.3390/ph4111400
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Hsp90 Inhibitor Drugs: A Complex Mosaic Emerges

Abstract: The molecular chaperone Hsp90 holds great promise as a cancer drug target, despite some of the initial clinical trials of Hsp90 inhibitor drugs having not lived up to expectation. Effective use of these drugs will benefit greatly from a much more detailed understanding of the factors that contribute to resistance, whether intrinsic or acquired. We review how cell culture studies have revealed a number of different mechanisms whereby cells can be rendered less susceptible to the effects of Hsp90 inhibitor treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 115 publications
(158 reference statements)
2
41
0
Order By: Relevance
“…HSP90 is a molecular chaperone that maintains the homeostasis of many different client proteins and consequently, HSP90 inhibition may block multiple oncogenic signaling pathways simultaneously (39,44). Several potential mechanisms of resistance have been described, including compensatory up-regulation of heat shock response by the transcription factor HSF1, involving particularly the pro-survival chaperones HSP70 and HSP27 (46). We confirm transcriptional upregulation of heat shock response in CMS4 cell lines after HSP90 inhibition, indicating a specific response to the targeted treatment.…”
Section: Discussionsupporting
confidence: 61%
“…HSP90 is a molecular chaperone that maintains the homeostasis of many different client proteins and consequently, HSP90 inhibition may block multiple oncogenic signaling pathways simultaneously (39,44). Several potential mechanisms of resistance have been described, including compensatory up-regulation of heat shock response by the transcription factor HSF1, involving particularly the pro-survival chaperones HSP70 and HSP27 (46). We confirm transcriptional upregulation of heat shock response in CMS4 cell lines after HSP90 inhibition, indicating a specific response to the targeted treatment.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this work, our previous studies indicated that the combined targeting of HSP90 and HSF1-mediated heat shock response could be an effective approach to enhance HSP90 inhibitor activities (13,41). However, the identification of approaches to target HSF1 remains a challenge.…”
Section: Discussionsupporting
confidence: 82%
“…The phosphorylated Hsp27 has been revealed to stabilize the protein translation factor eIF4E in androgene resistant prostate cancer cells [223]. Phosphorylated Hsp27 has also been involved in metastasis [224]. Recently, it has been shown that HSF-1 is an important facilitator of oncogenesis [221,225].…”
Section: Self Defence Mechanism Of Hsp90mentioning
confidence: 99%